High-parameter phenotypic characterization reveals a subset of human Th17 cells that preferentially produce IL-17 against M. tuberculosis antigen - Ogongo, Paul; Tran, Anthony; Marzan, Florence; Gingrich, David; Krone, Melissa; Aweeka, Francesca; Lindestam Arlehamn, Cecilia S.; Martin, Jeffrey N.; Deeks, Steven G.; Hunt, Peter W.; Ernst, Joel D. (Frontiers in Immunology, 2024)
Background Interleukin-17–producing CD4 T cells contribute to the control of Mycobacterium tuberculosis (Mtb) infection in humans; whether infection with human immunodeficiency virus (HIV) disproportionately affects distinct Th17-cell subsets that respond to Mtb is incompletely defined. Methods We performed high-definition characterization of circulating Mtb-specific Th17 cells by spectral flow cytometry in people with latent TB and treated HIV (HIV-ART). We also measured kynurenine pathway activity by liquid chromatography-mass spectrometry (LC/MS) on plasma and tested the hypothesis that tryptophan catabolism influences Th17-cell frequencies in this context. Results We identified two subsets of Th17 cells: subset 1 defined as CD4+Vα7.2−CD161+CD26+and subset 2 defined as CD4+Vα7.2−CCR6+CXCR3−cells of which subset 1 was significantly reduced in latent tuberculosis infection (LTBI) with HIV-ART, yet Mtb-responsive IL-17–producing CD4 T cells were preserved; we found that IL-17–producing CD4 T cells dominate the response to Mtb antigen but not cytomegalovirus (CMV) antigen or staphylococcal enterotoxin B (SEB), and tryptophan catabolism negatively correlates with both subset 1 and subset 2 Th17-cell frequencies. Conclusions We found differential effects of ART-suppressed HIV on distinct subsets of Th17 cells, that IL-17–producing CD4 T cells dominate responses to Mtb but not CMV antigen or SEB, and that kynurenine pathway activity is associated with decreases of circulating Th17 cells that may contribute to tuberculosis immunity.